Perencanaan Dan Pengendalian Anggaran Operasi (Studi Pada PT Berlian Laju Tanker Tbk. Tahun 2006-2017) - Handoyo Widyanto; Iswanto Iswanto (Majalah Ilmiah Bahari Jogja, 2019)
This research covers operating cost at PT Berlian Laju Tanker Tbk. the period 2006-2017. The problem being studied is operational cost control at PT Berlian Laju Tanker year 2006-2017. This research is quantitative descriptive. The data studied in this research is secondary data. The technique used is the method of documentation with quantitative descriptive analysis method. The study found that operational budget can not control operational budget effectively in PT Berlian Laju Tanker at 2006-2017 (unproved hypothesis). Because planned operational is not match with realization operational which is actual cost lower than actual requirement. This because the company try to cut the high costs, so the amount budgeted does not fit the needs. Indispensable, the company needs the costs. This is what causes the deviation of the realization of the operating budget.